2007
DOI: 10.1016/j.pain.2006.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Modality-specific sensory changes in humans after the induction of long-term potentiation (LTP) in cutaneous nociceptive pathways

Abstract: The impact of long-term potentiation (LTP) in nociceptive pathways on somatosensory perception was examined by means of quantitative sensory testing (QST) in the ventral forearm of 12 healthy human subjects. Electrical high-frequency stimulation of the forearm skin (HFS; 5 x 1 s at 100 Hz and 10 x detection threshold) led to an abrupt increase of pain to single electrical test stimuli, which were applied through the same electrode (perceptual LTP +72%, p<0.01). Perceptual LTP outlasted the 1-h observation peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
66
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 54 publications
20
66
1
2
Order By: Relevance
“…This shows that HFS induces both mechanical and heat secondary hyperalgesia, challenging the conclusions of Lang et al (2007) but supporting the results of other studies (Hardy et al 1950;Kilo et al 1994;Pedersen and Kehlet 1998;Serra et al 1998;Sumikura et al 2006). Importantly, the time course of the increased perception to laser stimuli after HFS was similar to the time course of the effect of HFS on the perception of punctate mechanical stimuli (Fig.…”
Section: Effect Of Hfs On the Responses To Thermal Stimulisupporting
confidence: 86%
See 1 more Smart Citation
“…This shows that HFS induces both mechanical and heat secondary hyperalgesia, challenging the conclusions of Lang et al (2007) but supporting the results of other studies (Hardy et al 1950;Kilo et al 1994;Pedersen and Kehlet 1998;Serra et al 1998;Sumikura et al 2006). Importantly, the time course of the increased perception to laser stimuli after HFS was similar to the time course of the effect of HFS on the perception of punctate mechanical stimuli (Fig.…”
Section: Effect Of Hfs On the Responses To Thermal Stimulisupporting
confidence: 86%
“…It has been suggested that the heterotopic hyperalgesia induced by HFS is primarily mediated through a selective enhancement of the synaptic transmission of mechanical nociceptive input (Klein et al 2008). This notion is based on the results of Lang et al (2007), who found that HFS reduces pain thresholds to mechanical stimuli without concomitantly inducing changes in heat pain thresholds. However, they did not actually measure the intensity of the percept elicited by thermonociceptive stimuli.…”
mentioning
confidence: 99%
“…Further studies are required to confirm this observation; nevertheless, the present findings suggest that the ipsilateral pain-inhibitory influence evoked by electrical stimulation of the forearm acted more strongly on thermal than mechanical nociceptors. This might explain why secondary hyperalgesia developed more readily to mechanical than thermal stimuli after electrical stimulation in this and previous studies (Klein et al 2008;Lang et al 2007;Vo and Drummond 2013b, a).…”
Section: Analgesia To Blunt Pressure In the Foreheadsupporting
confidence: 56%
“…Preferential activation of nociceptors by HFS increases synaptic strength and evokes long-term potentiation in spinal nociceptive pathways (Klein et al 2008;Lang et al 2007;Pfau et al 2011;van den Broeke et al 2010). However, HFS may also evoke activity in paininhibitory pathways that descend from the brainstem to all levels of the spinal cord (Sandkuhler and Liu 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that high frequency CES (more than 2 bursts at 100 Hz) (Liu and Sandkühler, 1997;Benrath et al, 2005), intermediate frequency CES (10 Hz for 1 sec repeated 12 times at 10 sec interval; 10 Hz for 10 sec) (Terman, 2001;Kim et al, 2015) and even low frequency CES (1~2 Hz for several minutes) (Ikeda et al, 2006;Drdla and Sandkühler, 2008;Kim et al, 2015) of primary afferent C-fibers can induce LTP at the first nociceptive synapses in vivo and in vitro. However, in human subjects the most frequently used paradigm for inducing similar LTP-like pain amplification including homotopic pain-LTP and heterotopic pain-LTP (secondary hyperalgesia) is 1 ms square pulses presented at 100 Hz for 1 sec, repeated 5 times with 10 sec intervals using a special epicutaneous electrode (Klein et al, 2004(Klein et al, , 2006Hansen et al, 2007;Lang et al, 2007;Pfau et al, 2011;van den Broeke et al, 2014 a,b). In contrast, the very low frequency (1 Hz) induced perceptual LTD (long-term depression) rather than LTP (Klein et al, 2004;Rottmann et al, 2010).…”
Section: Introductionmentioning
confidence: 99%